Circulating tumour cells as a potential biomarker for lung cancer screening: a prospective cohort study. Issue 7 (July 2020) - Marquette, Charles-Hugo; Boutros, Jacques; Benzaquen, Jonathan; Ferreira, Marion; Pastre, Jean; Pison, Christophe; Padovani, Bernard; Bettayeb, Faiza; Fallet, Vincent; Guibert, Nicolas; Basille, Damien; Ilie, Marius; et al.
Summary: Background: Lung cancer screening with low-dose chest CT (LDCT) reduces the mortality of eligible individuals. Blood signatures might act as a standalone screening tool, refine the selection of patients at risk, or help to classify undetermined nodules detected on LDCT. We previously showed that circulating tumour cells (CTCs) could be detected, using the isolation by size of epithelial tumour cell technique (ISET), long before the cancer was diagnosed radiologically. We aimed to test whether CTCs could be used as a biomarker for lung cancer screening. Methods: We did a prospective, multicentre, cohort study in 21 French university centres. Participants had to be eligible for lung cancer screening as per National Lung Screening Trial criteria and have chronic obstructive pulmonary disease with a fixed airflow limitation defined as post-bronchodilator FEV1/FVC ratio of less than 0·7. Any cancer, other than basocellular skin carcinomas, detected within the previous 5 years was the main exclusion criterion. Participants had three screening rounds at 1-year intervals (T0 [baseline], T1, and T2), which involved LDCT, clinical examination, and a blood test for CTCs detection. Participants and investigators were masked to the results of CTC detection, and cytopathologists were masked to clinical and radiological findings. Our primary objective was to test the diagnostic performance of CTC detection using the ISET technique in lung cancer screening, compared with cancers diagnosed by final pathology, or follow up if pathology was unavailable as the gold standard. This study is registered with ClinicalTrials.gov identifier, number NCT02500693 . Findings: Between Oct 30, 2015, and Feb 2, 2017, we enrolled 614 participants, predominantly men (437 [71%]), aged 65·1 years (SD 6·5), and heavy smokers (52·7 pack-years [SD 21·5]). 81 (13%) participants dropped out between baseline and T1, and 56 (11%) did between T1 and T2. Nodules were detected on 178 (29%) of 614 baseline LDCTs. 19 participants (3%) were diagnosed with a prevalent lung cancer at T0 and 19 were diagnosed with incident lung cancer (15 (3%) of 533 at T1 and four (1%) of 477 at T2). Extrapulmonary cancers were diagnosed in 27 (4%) of participants. Overall 28 (2%) of 1187 blood samples were not analysable. At baseline, the sensitivity of CTC detection for lung cancer detection was 26·3% (95% CI 11·8–48·8). ISET was unable to predict lung cancer or extrapulmonary cancer development. Interpretation: CTC detection using ISET is not suitable for lung cancer screening. Funding: French Government, Conseil Départemental 06, Fondation UNICE, Fondation Aveni, Fondation de France, Ligue Contre le Cancer-Comité des Alpes-Maritimes, ARC (Canc'Air Genexposomics), Claire de Divonne-Pollner, Enca Faidhi, Basil Faidhi, Fabienne Mourou, Michel Mourou, Leonid Fridlyand, cogs4cancer, and the Fondation Masikini.